Electronic analysis of hydrogen-bonded molecular complexes: the case of DNA sensed in a functionalized nanogap. Issue 4 (17th January 2023) - Maier, Frank C.; Fyta, Maria
Abstract : Relative arrangements within a hybrid complex of a probe nanoparticle and a target biomolecule strongly control the quantum transport across a nanogap these are placed in. Abstract : DNA nucleotides can be interrogated by nanomaterials in order to be detected. With the aid of quantum-mechanical simulations, we unravel the intrinsic details of the electronic transport across nanoelectrodes functionalized with tiny modified diamond-like molecules. These electrodes generate a gap in which DNA nucleotides are placed and can be identified. The identification is strongly affected by the hydrogen bonding characteristics of the diamond-like particle and the nucleotides. The results point to the connection of the electronic transmission across the functionalized nanogap and the electronic and bonding characteristics of the molecular complexes within the nanogap. Specifically, our discussion focuses on the influence of the DNA dynamics on the electronic signals across the nanogap. We identify the molecular complex's details that hinder or promote the electronic transport through an analysis that moves from the bonding within the molecular complex up to the electronic current that this can accommodate. Accordingly, our work discusses pathways for analyzing hydrogen-bonded molecular complexes or molecules hydrogen-bonded to a material part having the optimization of the design of biosensing nanogaps and read-out nanopores in mind. The presented approach, though, is applicable to a wide range of applications utilizing exactly the bio/nano interface.